Molecular targeted therapy for metastatic colorectal cancer: current and evolving approaches - Li, Furong; Lin, Yanping; Li, Rong; Shen, Xin; Xiang, Mengying; Xiong, Guangrui; Zhang, Ke; Xia, Tingrong; Guo, Jiangyan; Miao, Zhonghui; Liao, Yedan; Zhang, Xuan; et al. (Frontiers in Pharmacology, 2023)
Colorectal cancer (CRC) represents 10% of all cancer types, making it the third leading cause of cancer-related deaths globally. Metastasis is the primary factor causing mortality in CRC patients. Around 22% of CRC-related deaths have metastasis present at diagnosis, with approximately 70% of these cases recurring. Recently, with the application of novel targeted drugs, targeted therapy has become the first-line option for individualized and comprehensive treatment of CRC. The management of these patients remains a significant medical challenge. The most prevalent targeted therapies for CRC in clinical practice focus on anti-vascular endothelial growth factor and its receptor, epidermal growth factor receptor (EGFR), and multi-target kinase inhibitors. In the wake of advancements in precision diagnosis and widespread adoption of second-generation sequencing (NGS) technology, rare targets such as BRAF V600E mutation, KRAS mutation, HER2 overexpression/amplification, and MSI-H/dMMR in metastatic colorectal cancer (mCRC) are increasingly being discovered. Simultaneously, new therapeutic drugs targeting these mutations are being actively investigated. This article reviews the progress in clinical research for developing targeted therapeutics form CRC, in light of advances in precision medicine and new molecular target drug discovery.